1984
DOI: 10.1200/jco.1984.2.10.1157
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional parameters affecting erythrocyte polyamine levels in cancer patients.

Abstract: Changes in erythrocyte polyamine levels during intravenous hyperalimentation in cancer and noncancer patients were determined, and the influence of host nutritional status on polyamine metabolism was analyzed. RBC putrescine (P less than .001), spermidine (P less than .01), and spermine (P less than .005) levels, and the putrescine-spermidine ratio (P less than .001) increased in the cancer group while no significant increases were noted in the noncancer group. The degree of malnutrition, based on body weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Therefore, it is possible that urinary excretion of polyamines is significantly related to liver metabolism, with a more advanced functional influence of this phenomenon in cancer patients depending on either elevated hepatic acute-phase reactions with increased liver protein synthesis (26), or a more advanced influence of cholestasis in many cancer patients with progressive disease. This interpretation has also support in a negative correlation between plasma albumin, a negative acute-phase reactant, and polyamine excretion in both the present and previous studies (27).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Therefore, it is possible that urinary excretion of polyamines is significantly related to liver metabolism, with a more advanced functional influence of this phenomenon in cancer patients depending on either elevated hepatic acute-phase reactions with increased liver protein synthesis (26), or a more advanced influence of cholestasis in many cancer patients with progressive disease. This interpretation has also support in a negative correlation between plasma albumin, a negative acute-phase reactant, and polyamine excretion in both the present and previous studies (27).…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have demonstrated high polyamine content in erythrocytes, indicating that changes in plasma concentration of red blood cells may relate to whole-body polyamine content (27). Anaemia is a strong promoter of cell proliferation in bone marrow and of the synthesis of growth factors such as erythropoietin.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion was also supported by the finding that the carbohydrate component in ordinary animal food pellets was a powerful stimulant of tumour cell proliferation by activating DNA synthesis, an effect which may be evoked by insulin (Westin et al, 1991a;Westin et al, 1991b). Changes in tumour DNA synthesis was reflected by alterations in ornithinedecarboxylase activity (ODC), which is rate limiting for polyamine synthesis (Russel, 1973;Pegg, 1988;Ota et al, 1984;Janne et al, 1978). Polyamines are probably endogenously produced growth factors, that without cell DNA synthesis and cellcycle traverse cannot proceed normally.…”
supporting
confidence: 49%
“…This observation may be related to a possible increase in tumor growth in patients given TPN treatment for cancer-related cachexia (Ota et al, 1984), where TPN increased RBC polyamines selectively in cancer patients but not in non-cancer patients.…”
Section: ; Mccannmentioning
confidence: 96%